Abordaje teórico con relación al TDAH en el entorno escolar (2020)
The main objective of the development of the research work was to carry out a theoretical approach in relation to ADHD in the school environment. For the fulfillment of this The exploratory documentary study was applied, which made it possible to address a series of research that has been carried out at the international and national level and from them have greater knowledge about the influence of the disorder under study on the process of learning of school-age children, that is, it could be determined that for To counteract these, it is essential that new methodologies be implemented by the teachers that lead to the inclusion of the child in the development of activities schoolchildren.